Innovation in Islamic Religious Education Learning in the Digital Era: Effective Design of the Flipped Learning Model - Saputra, Indrian; Anita, Fitri (Insight: Indonesian Journal of Social, Humanity, and Education, 2025)
This study aims to describe the application of the flipped learning model in Islamic Religious Education (PAI) learning and evaluate its effectiveness in increasing student involvement and independence. The method used is library research with a qualitative approach. Data were obtained from various literature sources, such as scientific journals, books, and relevant online articles, then analyzed descriptively. The results of the study indicate that the flipped learning model is able to change the learning pattern from teacher-centered to student-centered, where students study the material independently outside the classroom through video media, e-books, and other online content, then discuss it collaboratively in the classroom. This strategy increases active participation, understanding of concepts, and the use of technology in PAI learning. However, its effectiveness is highly dependent on technological readiness, teacher competence, and parental support. With good planning, this model can be a relevant learning alternative in the digital era.